Students’ intention towards entrepreneurship as a career: a case of university students / Kartini Mat Rashid ... [et al.] - Mat Rashid, Kartini; Shamsudin, Azlina; Abdullah, Nasiha; Johar, Norchahaya; Jusoh, Zuraini (Universiti Teknologi MARA, Perlis, 2021)
A part of the total unemployed in Malaysia is university graduates, while close to half of the graduates of public universities are working in mismatched occupations, totally unrelated to their formal training. To overcome this issue, the best solution is involvement in entrepreneurial activities. Therefore, this study aims to examine students’ intention towards entrepreneurship. The data were collected from questionnaires that have been distributed to diploma and degree students in UiTM Terengganu. The questionnaires were tested on 300 respondents. The study found that social environment and knowledge management are significant with student intention. The result for all independent variables shows a positive relationship with the dependent variable.